Clinico pathological aspects of solitary thyroid nodule: a hospital based prospective study - Rajendran, S.; Prabu, K. R. Manoj (International Surgery Journal, 2018)
Background: Nodular goitre is a common endocrine problem in the world today. Solitary thyroid nodule is defined as the presence of a palpable nodule in the otherwise normal thyroid gland. Solitary nodules are one of the most frequent presentations of thyroid disorder. The aim of this study was to study the incidence and other clinical parameters of solitary thyroid nodules and to correlate between clinical diagnosis and histopathological examination of solitary nodule thyroid. Methods: A prospective study was done in patients with solitary thyroid swelling, after taking a detailed history, were examined clinically and confirmed with FNAC and underwent thyroid surgery were included in this study. The histopathological reports were evaluated and correlated with clinical diagnosis by standard statistical methods. Results: Majority of the patients were between 21-30 years of age. Female:male ratio was about 11.5:1. Swelling in front of the neck was the most common presentation. Most common solitary thyroid swelling was the colloid goitre. Commonest surgery performed was hemithyroidectomy. Conclusions: The majority of the solitary nodule of the thyroid was found to be benign, and this illustrates that hemithyroidectomy is the preferred surgery unless malignancy is suspected by fine needle aspiration cytology.